ANALISIS POTENSI PENGEMBANGAN PARIWISATA BERKELANJUTAN DI KAMPUNG TAHIMA SOROMA (KAYO PULAU) DISTRIK JAYAPURA SELATAN KOTA JAYAPURA - Sudiro; Wairata, Juliani; T. Simbiak, Irja; Gultom, Ayub (POLITEKNIK LP3I JAKARTA, 2026)
Tahima Soroma Village (Kayo Pulo) in Jayapura City possesses unique natural and cultural potential, but it has not been optimally utilized for sustainable tourism. This study aims to analyze the potential for sustainable tourism in the region using a participatory approach involving indigenous communities as key actors. The researchers employed a descriptive-exploratory research method. The data analysis methods used in this study included theme analysis, data triangulation, and stakeholder mapping. The results are expected to identify the economic potential of tourism in increasing Jayapura City's Regional Original Income (PAD) through tourism levies, local job creation, and micro-enterprise development. Furthermore, this study also examines challenges such as limited infrastructure and low community participation. This research is expected to serve as a reference for stakeholders involved in sustainable tourism. Furthermore, the results can increase community participation in sustainable tourism management in Tahima Soroma Village. The output of this study will be the availability of references regarding the tourism potential of Tahima Soroma Village, South Jayapura District.